2012
DOI: 10.1103/physrevb.85.134510
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the optical properties of La2xBaxCuO4

Abstract: The optical properties of single crystals of the high-temperature superconductor La2−xBaxCuO4 have been measured over a wide frequency and temperature range for light polarized in the a-b planes and along the c axis. Three different Ba concentrations have been examined, x = 0.095 with a critical temperature Tc = 32 K, x = 0.125 where the superconductivity is dramatically weakened with Tc ≃ 2.4 K, and x = 0.145 with Tc ≃ 24 K. The in-plane behavior of the optical conductivity for these materials at high tempera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
50
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 139 publications
8
50
0
Order By: Relevance
“…To generate this large a response, we conclude that all parts of the sample must contribute to the signal, ruling out macroscopic phase separation. A previous optical conductivity study has shown that the superfluid density of this sample is consistent with the trend established for bulk superconductivity in all cuprate families in the form of Homes' law [19]. It thus appears that there must be local coexistence of the spin fluctuations and superconductivity.…”
supporting
confidence: 85%
“…To generate this large a response, we conclude that all parts of the sample must contribute to the signal, ruling out macroscopic phase separation. A previous optical conductivity study has shown that the superfluid density of this sample is consistent with the trend established for bulk superconductivity in all cuprate families in the form of Homes' law [19]. It thus appears that there must be local coexistence of the spin fluctuations and superconductivity.…”
supporting
confidence: 85%
“…2(c), appears to frustrate the interlayer Josephson coupling. A similar conclusion is indicated by optical conductivity studies [39,40]. Mean-field 2D superconductivity sets in at T 2D c together with the spin stripe order (T so ), with the resistivity staying finite until phase order is established at T BKT .…”
Section: Evidence For Coexisting Superconductivity and Stripe Ordersupporting
confidence: 72%
“…1). This feature in reflectance spectra of the peak+dip case looks similar that of electron underdoped cuprates and hole doped cuprates [7,5,34,32,6,8] (see also Fig. 5 for closer comparisons).…”
Section: Optical Conductivity and Reflectance Spectra Calculated Fromsupporting
confidence: 71%
“…(2). More explicitly we can write down the real and imaginary parts of the optical conductivity as a function of the real and imaginary parts of the optical self energy as [6] and with measured hole underdoped data of La 1.875 Ba 0.125 CuO 4 (middle column) [32,8]. In the middle column the scales on the vertical axis are shown on the right side.…”
Section: Optical Conductivity and Reflectance Spectra Calculated Frommentioning
confidence: 99%